(3CSGdjH bjGS bjeI GdeYdheGJ (B:s (3OQGSGJ h JWHjbGJ (B/s - (3GdTgQHdj, GfYGe Ydj Jhajbs ((3YeGf(B: s (3OGQ GdhQGb(B, s, 2010)
(3bjeI GdeYdheGJ aj GdJaGYd GdGdcJQhfj ef efXhQ GdfXQjI GdQjGVI ddeYdheGJ fehPL HQGZeGJj , EJLGgGJ GdLhOI aj fXe GdeYdheGJ GdeMhSHI , bjGS EfJGLjI GdYed GdeYdheGJj h eQhfJg aj fXe GdeYdheGJ , EbJUGOjGJ GdeYQaI GdLOjOI h NGUjI GdbjGS aj EYGOI gfOSI GdYedjGJ (B: (3bGfhf HGQjJh fhePLG GdbjGS h GdJWHjb , GdeYdheGJ GdGSJTGQjI aj MGdGJ Gdbje GdGSJgdGcjI , bhGYO JbOje GdNOeGJ h CKQgG aj LhOI NOeI GdHMK GdBdj , GdHQeLI GdNWjI h GdJaSjQ GdGbJUGOj aj Jbjje GdYed Gdafj GdeYdheGJj , GdVHW h GdJMce aj bhGYO GdHjGfGJ , GdJUfja GdBdj , bjGS caGAI fXe GSJQLGY GdeYdheGJ(B.s
(3eQGLY U(B.277s
Keywords: (3GdHK GdEfJbGFj ddeYdheGJs; (3GdeYdheGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s